Development and Validation of a Measurement to Assess College Students' Reactions to Faculty Incivility. Issue 8 (16th November 2016) - Itzkovich, Yariv; Alt, Dorit
Abstract : This study was aimed at constructing and validating a measurement to assess students' responses to faculty incivility (FI). A mixed-method approach was implemented. A qualitative method was used to analyze responses to FI as described by college students. The results foregrounded four categories— exit, voice, loyalty, and neglect —in line with the theoretical EVLN model for describing reactions to stressful conditions (such as, but not limited to, incivility). The students' descriptions were formulated as short items. Following the qualitative results, a quantitative method was used to validate the developed EVLN questionnaire and to assess the relationships between student characteristic variables (mainly, religious affiliation), experiences of FI (active FI and passive FI), and the four EVLN responses. Data were gathered from 744 undergraduate college students, yet only those who experienced FI to some extent were selected to assess reactions to FI. According to the structural equation modeling results, FI was positively linked solely to the exit response. In addition, the findings indicated that merely the active FI subfactor was linked to the exit factor. Interpretation of these results, their congruence within the context of the theoretical frameworks, limitations, and practical implications are discussed.